Gegenwart aus Jahrtausenden : Zeitgenössische Kunst aus Ägypten - von Roques, Karin Adrian; Ronte, Dieter; Wells, William; Krause, Norbert Fritz; El Saddik, Wafaa; Gras, Claudia; Kunstmuseum Bonn (Bonn : Kunstmuseum Bonn, 2007)
El Wahab, Emad Abd ; Abla, Mohamed ; Darwish, Wael ; Fikry, George ; Hafez, Khaled ; Lutfi, Huda ; Nabil, Youssef ; Naim, Sarah ; El Noshokaty, Shady ; Ramadan, Ayman ; El Semary, Ayman ; et al.
Kunstmuseum Bonn, Bonn, August 30 - October 28, 2007
kunstcatalogus
Keywords: Egypte